Socio-economic transformation of Poland’s largest cities over the years 1998–2008: A multivariate approach - Mierzejewska, Lidia (Rozwój Regionalny i Polityka Regionalna, 2013)
This article seeks to show changes in the socio-economic structure of the thirty largest Polish cities, in topological relations, and in the type of socio-economic differences among them. The research was carried out at three analytical levels: of the unitary variables chosen, principal components, and in a synthetic approach (cluster analysis). To assess structural changes, use was made of comparative statics involving an analysis of the 1998 and 2008 situations. The period analysed was one of dynamic changes in the determinants of the socio-economic development of Polish cities, with four reforms of key significance being introduced, not all of them crowned with success, but also a period marking the start of a decline in demographic dynamics and of suburbanisation processes. It is also treated as a time of transition from a quantitative to a qualitative type of urban development, as indicated by improving services in the sphere of municipal infrastructure. Those processes are connected with the restructuring of the economy, in particular with its distinctly post-industrial orientation, which is especially readily visible in the case of the Upper Silesian Industrial District (a mining and heavy-industry region). The research corroborated the highly specific type of development of the towns of this region as well as the unique position of the Polish capital city. It also showed that the changes which determined the tendencies of transformation of the Polish cities were mainly those in demography, housing situation, level of health care, and level of entrepreneurship.